Chad s gum makes a come-back - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Gum arabic, an extract of the tree Acacia senegal, is regaining interest after alternative products have fallen into discredit: gelatine fell from consumer favour after the 'mad cow' scandal, and starches too, in the light of the debates about...